Analysis on the potential of Pennisetum hydridum for phytoremediation of Cd-polluted soil fertilized by worm castings - Xiafang Hong; Zhi Zhang; Zhiwei Wan (PLoS ONE, 2025)
Soil heavy metal pollution including Cd, is the main factor that causes the decline of ecological environment quality, the excessive content in crops and the harm to human health. Phytoremediation is one of the important ways to control heavy metals, which has both ecological and economic benefits. However, most plant species have limited remediation ability and cannot achieve good heavy metal removal effect. In contrast, P. hydridum, easy to cultivate, has large biomass and short growth cycle, shows strong restoration ability in the treatment of heavy metal polluted soil. In order to explore its phytoremediation in Cd-polluted soils under appropriate agronomic measures, this experiment adopts the field random block experiment design to study the control effect and application safety of the application of organic fertilizers (warm castings and biogas slurry) to plant it in the Cd-polluted farmland. The results showed the Cd in the soil after P. hydridum harvesting was 0.53–0.56 mg/kg, and the partial Cd in the shoot was 0.21–0.28 mg/kg (fresh weight), and the enrichment coefficients were all greater than 1, and the extraction amount and efficiency of Cd were 7.17–9.43 mg/m2 and 5.71%–7.01%, respectively. All those data express a decrease in Cd under various treatment conditions, indicating that, P. hydridum can grow under high concentration and it has a certain enrichment effect on Cd, especially in the application of organic fertilizers, which could not only improve the growth performance of the plant, but also improve the soil, much better than that of other Cd hyper-accumulators. Moreover, the positive correlation between the biomass allocation rate and Cd in the soil reflects that the biomass allocation of the plant behaved in different ways with the increase of Cd oil. It is also feasible in terms of application safety due to a long and gradual process to enrich Cd in soil. This study made a proof that it would be a green and environmentally friendly treatment method by making good use of its high biomass to adsorb and remove heavy metals from soil, which would have a good application prospect and development value.